The Principle of the Inadmissibility of Arbitrary Interference in Family Affairs - A. Ya. Ryzhenkov (Сибирское юридическое обозрение, 2020)
The article investigates one of the fundamental principles of family law aimed at clarifying the boundaries between legal and arbitrary interference of the state and third parties in the affairs of the family. The Author argues that acts committed in accordance with the law and contrary to the principle of proportionality and proportionality do not constitute arbitrary interference in the affairs of the family. It is noted that at the moment the normative implementation of the principle of prohibition of voluntary interference in family affairs is controversial. On the one hand, the decriminalization of family violence is decreasing interference of state and society in the family business, on the other hand, we see the strengthening of the role of the juvenile justice system, which means the increase of state intervention in the affairs of the family.